(untitled) (Boston, 2017)
This book is a standalone book and will not include any access codes. Considered the classic source in its field, DIRECT SOCIAL WORK PRACTICE: THEORY AND SKILLS prepares you for effective real-world practice. Packed with case examples, illustrations, and proven learning experiences from the authors and other social work practitioners, the book integrates the major theories and skills that direct social work practitioners need to understand and master. Part of the Brooks/Cole Empowerment Series, the tenth edition is completely up to date and thoroughly integrates the core competencies and recommended practice behaviors outlined in the 2015 Educational Policy and Accreditation Standards (EPAS) set by the Council on Social Work Education (CSWE).
Thực hành công tác xã hội,Công tác xã hội
Keywords: Social service,Social service,Dịch vụ xã hội; United States,Hoa Kỳ